2017
DOI: 10.1002/prep.201700092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Poly(glycidyl nitrate-block-caprolactone-block-glycidyl nitrate) (PGN-PCL-PGN) Tri-Block Copolymer as a Novel Energetic Binder

Abstract: An energetic binder was synthesized through ring opening copolymerization of glycidyl nitrate (GLYN) with polycaprolactone (PCL) as a macroinitiator to form tri‐block copolymer PGN‐PCL‐PGN. Effect of monomer concentration, catalyst, reaction time and solvent was investigated in polymerization. Resulting tri‐block copolymer was characterized by Fourier transform infrared spectroscopy (FT‐IR), nuclear magnetic resonance spectroscopy (NMR), gel permeation chromatography (GPC), differential scanning calorimetry (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The molecular structures of PGN, PNIMMO and P(GN/NIMMO) were confirmed by 1 H NMR and shown in Figure 2. In the 1 H NMR spectra of PGN, the signals at approximately 3.36-4.06 ppm were ascribed to the methylene and methine protons, and the peaks at about 4.37-4.64 ppm belong to the methylene 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 protons of the ÀCH 2 ONO 2 [6,16]. In the 1 H NMR spectra of PNIMMO, the single peak at 1.00 corresponded to the methyl protons, the multi-peaks at about 3.23-3.30 ppm were ascribed to the methylene protons, and the peaks at about 4.39 ppm belong to the methylene protons of the -CH 2 ONO 2 [3,17].…”
Section: H Nmr Analysismentioning
confidence: 99%
“…The molecular structures of PGN, PNIMMO and P(GN/NIMMO) were confirmed by 1 H NMR and shown in Figure 2. In the 1 H NMR spectra of PGN, the signals at approximately 3.36-4.06 ppm were ascribed to the methylene and methine protons, and the peaks at about 4.37-4.64 ppm belong to the methylene 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 protons of the ÀCH 2 ONO 2 [6,16]. In the 1 H NMR spectra of PNIMMO, the single peak at 1.00 corresponded to the methyl protons, the multi-peaks at about 3.23-3.30 ppm were ascribed to the methylene protons, and the peaks at about 4.39 ppm belong to the methylene protons of the -CH 2 ONO 2 [3,17].…”
Section: H Nmr Analysismentioning
confidence: 99%
“…Generally, it can be divided into two categories. The one kind contains azide, such as glycidyl azide polymer , 3,3‐bis(azidomethyl)oxetan ; the other kind contains nitrate, such as nitrated HTPB , polyNIMMO and polyGLYN .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, polytriazole adhesive has good compatibility and interface binding force with polar plasticizers or oxidants due to its polarity. In addition, the combustion of triazole structure produces nitrogen and generates a lot of energy to improve the balance of energy and oxygen [14][15][16]. Qu's team [17] reported that polytriazole elastomers prepared from polymer with terminal alkynyl groups cured by azide compounds showed a high performance of mechanical properties including tensile strength of 0.76 MPa and elongation at break of 120 %.…”
Section: Introductionmentioning
confidence: 99%